2011
DOI: 10.1212/wnl.0b013e31821670fb
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz associated with cognitive disorders in otherwise asymptomatic HIV-infected patients

Abstract: A high prevalence of HAND was observed in apparently asymptomatic HIV+ individuals. HAND was associated with efavirenz use, suggesting the potential neurotoxicity of this drug. Routine neuropsychological examinations could help clinicians make correct diagnoses and manage mild, but clinically relevant, forms of HAND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
163
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(183 citation statements)
references
References 24 publications
14
163
6
Order By: Relevance
“…Furthermore being on efavirenz was independently associated with the diagnosis of HAND in a cohort of stable HIV-positive patients. [200] One recent study reported that cognition improved for up to 96 weeks in a group of immunologically and virologically stable patients who elected to come off treatment; the improvement was significant in all participants but greater in efavirenz recipients. [133] These results raise the possibility that ARVs concentrations to some extent may have some detrimental effects: this may be particularly relevant for individuals with specific genetic profiles but it must be compared to the clear beneficial effect of HAART on compartmentalized viral control.…”
Section: Arv Toxicity In the Cnsmentioning
confidence: 99%
“…Furthermore being on efavirenz was independently associated with the diagnosis of HAND in a cohort of stable HIV-positive patients. [200] One recent study reported that cognition improved for up to 96 weeks in a group of immunologically and virologically stable patients who elected to come off treatment; the improvement was significant in all participants but greater in efavirenz recipients. [133] These results raise the possibility that ARVs concentrations to some extent may have some detrimental effects: this may be particularly relevant for individuals with specific genetic profiles but it must be compared to the clear beneficial effect of HAART on compartmentalized viral control.…”
Section: Arv Toxicity In the Cnsmentioning
confidence: 99%
“…This finding was expected, given the improved CSF VL control. However, Rourke et al [19] and Ciccarelli et al [20] found no association between CPE scores and cognitive outcomes. In this regard it is important to remember that CSF VL is not necessarily equivalent to brain VL.…”
Section: Follow-up Assessments N=121mentioning
confidence: 99%
“…Some of the above studies have been done using ART-naïve participants, [18,19] and others naïve and experienced participants. [20][21][22] Not all studies measured both CSF VL response and cognitive outcomes. Tozzi et al [18] noted that the correlation between higher CPE score and neuropsychological improvement was exclusive to those who achieved CSF VL suppression.…”
Section: Follow-up Assessments N=121mentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms may result in patients having a poorer cognitive performance. This hypothesis is supported by a recent study reporting that efavirenz is associated with cognitive disorders in otherwise asymptomatic HIV-infected patients (20). Other previously reported risk factors for HAND include a decreased CD4 count, anemia, declining platelet count, high HIV-RNA viral load in the CNS, and hepatitis C coinfection (20)(21)(22).…”
Section: Discussionmentioning
confidence: 59%